A study on TikTok platform on university students' purchasing behaviour - Tan, Wei Leng (2024)
The rise of social media platforms following the pandemic caused a shift in consumer behaviour, particularly among younger demographics. Consumers are shifting from making purchases in physical stores to online stores, including live-streaming and sites like Shopee and Lazada. TikTok is a social media platform that is widely used among teenagers, it has over 1.677 billion users globally, and out of 1.1 billion are active users in 2023. TikTok allows users to share short videos and has gained a lot of popularity because of its interesting and diverse user-generated content. Social media users were using TikTok for an average of 55.8 minutes in 2023. Marketers take it as a media to reach their brand and services to users via short videos and live streaming. Companies follow the trend and leverage the platform to market their products and services in novel ways by using content creators to promote their brands. Understanding how TikTok influences viewers' purchasing decisions is crucial as long as the platform is able to attract younger audiences. This study aims to examine the impact of usergenerated content on buying attention and determine TikTok content elements, such as engagement tactics, influencer endorsements, and product presentations on viewer’s buying behaviour. The descriptive quantitative method is used in this study. Using a purposive sampling technique, the study's sample of 100 respondents was selected based on specific criteria, including those between the ages of 18 and 30 who use TikTok for social media.